ANALISIS SIFAT FISIKA TANAH GAMBUT PADA HUTAN GAMBUT DI KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - SUSANDI SUSANDI; OKSANA OKSANA; AHMAD TAUFIQ ARMINUDIN (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The research was conducted on January to April 2013 in the secondary forest Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province. This study was done by observation and survey on 0-50 cm, 50-100 cm, and 100-150 cm of land depth to analysis peat thickness, depth of water table, the colour of peat, peat maturity, bulk dencity, and water content. Results showed that the peat was have more than 6 m depth. Thickness of water table average was 30.75 cm, soil colour black ground colour reddish, very dull red, and dark brown. The decomposition degree of peat on 0-50 cm and, 50-100 cm were hemik (fiber content 41% and 61%), whereas 100-150 cm was fibric (fiber content 70.25%). Bulk dencity of 0-50 cm, 50-100 cm and 100-150 cm depth were 0.15 gr/cm3, 0.125 gr/cm3, and 0.105 gr/cm3. Water content of 0-50 cm, 50-100 cm, and 100-150 depth were 541.82%, 719.41%, and 888.30%.